Consistent tangent matrices of curved contact operators involving anisotropic friction - Alart, Pierre; Heege, Andreas (European Journal of Computational Mechanics, 1995)
Contact problems involving friction are difficult to solve because they are governed by multivalued tribological laws. Using a mixed penalty-duality formulation, a generalized Newton method has proved to be efficient. In order to introduce new nonlinearities like anisotropic friction and curvature of the contact surface, appropriate tangent matrices have to be derived. The additional terms are discussed and algorithms are proposed when analytical expressions are not available. Two numerical tests are presented to show the performance of the generalized Newton method.